Forum for Arctic Modeling and Observational Synthesis (FAMOS): Past, current, and future activities. Issue 6 (3rd June 2016) - Proshutinsky, A.; Steele, M.; Timmermans, M.‐L.
Abstract: The overall goal of the Forum for Arctic Modeling and Observational Synthesis (FAMOS) community activities reported in this special issue is to enhance understanding of processes and mechanisms driving Arctic Ocean marine and sea ice changes, and the consequences of those changes especially in biogeochemical and ecosystem studies. Major 2013–2015 FAMOS accomplishments to date are: identification of consistent errors across Arctic regional models; approaches to reduce these errors, and recommendations for the most effective coupled sea ice‐ocean models for use in fully coupled regional and global climate models. 2013–2015 FAMOS coordinated analyses include many process studies, using models together with observations to investigate: dynamics and mechanisms responsible for drift, deformation and thermodynamics of sea ice; pathways and mechanisms driving variability of the Atlantic, Pacific and river waters in the Arctic Ocean; processes of freshwater accumulation and release in the Beaufort Gyre; the fate of melt water from Greenland; characteristics of ocean eddies; biogeochemistry and ecosystem processes and change, climate variability, and predictability. Future FAMOS collaborations will focus on employing models and conducting observations at high and very high spatial and temporal resolution to investigate the role of subgrid‐scale processes in regional Arctic Ocean and coupled ice‐ocean and atmosphere‐ice‐ocean models. Key Points: This is an introduction to the JGR FAMOS issue summarizing 3 year study results Coordinated experiments improved models and investigated ocean, ice, and ecosystem processes FAMOS collaborations are an important and unique component of present‐day Arctic studies